(untitled) (Research, Society and Development, 2023)
Objective: the objective of this study is to facilitate care related to patients with Post-Polio Syndrome (PPS) to be assisted according to qualifications and functions of nursing care. Methodology: This is an integrative review study of a descriptive nature. Data were searched through the following electronic means: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS) Medical Literature Analysis and Retrieval System Online (MEDLINE), PUBMED, an academic search engine Google Scholar and along with a standalone web search tool using Google. The following descriptors were used for research in Portuguese, "Post-Poliomyelitis Syndrome", "Nursing care" and "Rehabilitation", in English, "Postpoliomyelitis Syndrome" "Nursing Care" and "Rehabilitation", and the last language chosen was the Spanish with “Síndrome Pospoliomielitis”, “Cuidado de Enfermera” and “Rehabilitación”, using the Boolean operators “and” and “or” for their crossing. The inclusion criteria were to keep articles between the years 2006 to 2023, which covered the theme, associated with Portuguese, English and Spanish. As for the exclusion criteria, excluding repeated databases, reviews, abstracts, theses and records that deviated from the proposed theme. Results: 17 records were found, which were adapted and covered the theme of this study, on nursing care for patients with PPS. Conclusion: There is a national literature shortage on the subject, however, care was adapted according to the assumptions and competencies of nursing that can be used individually or multidisciplinary.